Performance evaluation of hybrid electrocoagulation process parameters for the treatment of distillery industrial effluent - Asaithambi, P.; Sajjadi, B.; Abdul Raman, Abdul Aziz; Daud, Wan Mohd Ashri Wan (Institution of Chemical Engineers, 2016)
A hybrid electrocoagulation process using iron electrode was developed for removal of organic pollutants from distillery industrial effluent. Combinations of electrocoagulation process with different advanced oxidation processes such as electrocoagulation, photo–electrocoagulation, peroxi–electrocoagulation and peroxi–photo–electrocoagulation processes investigated and compared in terms of color removal, Chemical Oxygen Demand (COD) removal and electrical energy consumption. An overall COD removal efficiency of 85% with 1.20 kWh/m3 of energy consumption, current density of 0.13 A/dm2, initial COD concentration of 2500 ppm, initial pH of 7, H2O2 concentration of 234 mg/L, stirring speed of 100 rpm and reaction time of 240 min was observed in the peroxi–electrocoagulation process. The effects of different operating parameters such as initial pH of the effluent (3–11), current density (0.03–0.23 A/dm2) and concentration of H2O2 (58.5–585 mg/L) on color removal, COD removal and electrical energy consumption were studied. The direct- and alternating-current electrocoagulation processes were also studied.